DEVELOPMENT OF REAL TIME AIR QUALITY MONITORING SYSTEM - ZAINI, AHMAD AIDEED (Universiti Teknologi PETRONAS, 2017)
This dissertation presents a project entitled Development of Real Time Air Quality Monitoring System, which generally a project that develop a device that capable to detect and measure the air pollution index (API) in the surrounding area. The device developed is cheaper in cost, portable and reliable capability. The project strategy is to integrate the sensor components for detection and measurement, communication module for information output into the Arduino Microcontroller. The measurement is synchronized to the API system used in Malaysia and global Air Quality Index (AQI) system exclusively for PM2.5 sensor.